Momentary Associations of Osteoarthritis Pain and Affect: Depression as Moderator. (5th December 2021) - Parmelee, Patricia A; Behrens, Emily A; Costlow Hill, Kyrsten; Cox, Brian S; DeCaro, Jason A; Keefe, Francis J; Smith, Dylan M
Abstract: Objectives: This research examined main and moderating effects of global depressive symptoms upon in-the-moment associations of pain and affect among individuals with knee osteoarthritis (OA). Effects of depression on short-term change in pain and affect were also examined. Method: Older adults with physician-confirmed OA ( N = 325) completed a baseline interview tapping global depressive symptoms, followed by an experience sampling protocol that captured momentary pain and affect 4 times daily for 7 days. Multilevel models controlling demographics and health conditions examined main and moderating effects of depression on momentary associations of pain with positive affect (PA) and negative affect (NA). Similar methods addressed short-term change in pain and affect. Auxiliary analyses explored broad associations of depressive symptoms with person-level averages and variability in pain and affect. Results: Global depression predicted current pain, PA, and NA, as well as change in pain and affect over a 3- to 8-h period. Furthermore, both in the moment and over short periods, the association of pain and NA was stronger among persons higher in depressive symptoms. No moderating effect for the PA–pain association was found. Depressive symptoms were also associated with variability in pain and affect, particularly NA. Discussion: Results confirm previous work on the relation of chronic pain with both global depressive symptoms and short-term affect. This research further demonstrates a unique moderating role of depression on the association of momentary pain with NA and suggests that the causal path may be stronger from pain to affect than vice versa.